GENERALIZED FACTORIAL POWERS AND SOME OF ITS APPLICATIONS - Заторський, Роман Андрійович; Гой, Тарас Петрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We consider the identities of generalized factorial powers. In particular, we generalized polynomial formula for arbitrary finite number of terms. The connection of some non-elementary real functions generated by rising factorials with the generalized hypergeometric function is established.